The Portrayal of Woman Image in the Arabic Language Textbooks for the Basic Stage in Jordan: An Analytical Study (Mutah Journal of Humanities and Social Sciences (MJHSS), 2024)
The study aimed to show the image of woman portrayed in the Arabic language textbooks for the primary stage in the schools of Jordan. The sample of the study consisted of all the Arabic language textbooks assigned for students in the primary stages of schools in Jordan, which included )26( textbooks. To achieve the goals of the study, a tool was prepared consisting of six areas: educational role of woman, social and familial roles of woman,, political and national roles, professional roles, religious and historical roles, the personalization of women. checking The validity and reliability of the instrument of the study were checked. The results of the study showed that the social and familial roles of women came first with a frequency of (88) and a percentage of (39%), followed by educational roles with a frequency of (75), and a percentage of (29%), then professional roles with (46) recurrences and a percentage of (18%), next historical and religious roles, with (25) recurrences and a percentage of (10%), and political and national roles came last with a frequency of 24 and by percentage of (9%). The analysis also showed that the marital status of the woman was concentrated in the wife only, and no other cases were revealed, and the results showed that the woman’s personality got the highest frequency in the six areas. It got (105) recurrences, and it was led by the woman who is characterized by responsibility. It obtained the highest frequency (24%),
Keywords: Image of Woman; Arabic Language Textbooks; Primary School